Pengaruh Model Pembelajaran Student Teams Achievement Divisions (STAD) pada Pembelajaran Jarak Jauh terhadap Kemampuan Penalaran Matematis Di SMPIT Avicenna Bekasi Utara: Pengaruh Model Pembelajaran Student Teams Achievement Divisions (STAD) - Azzahrah, Fathimah (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2020)
This study was conducted to determine whether there is an effect of the STAD learning model on distance learning on students' mathematical reasoning abilities. The research was carried out at Avicenna Junior High School, North Bekasi in the seventh grade of the even semester of the 2020/2021 school year on the subject of Quadrilaterals and Triangles. The research method used is quasi-experimental. Sampling using simple random sampling technique. Simple random sampling technique is done by randomly selecting two classes from four classes that are normally distributed, homogeneous, and have the same average to be used as the experimental class (STAD type cooperative learning model) and control class (conventional learning model). The research instrument used was a final test of mathematical reasoning abilities on the subject of quadrilaterals and triangles as many as 6 items of description that had passed content, construct and empirical validity tests. Based on the test results of pre-treatment data analysis prerequisites, the experimental class and control class were normally distributed and homogeneous. Therefore, the statistical hypothesis testing used a t-test with a significance level of = 0.05. Based on the calculation of statistical hypotheses, = 2.8075 and = 1.6772. The value of > . so reject 0 and it can be concluded that there is a difference in the average scores of students' mathematical reasoning abilities, with the average mathematical reasoning ability test scores of experimental class students being higher than those of the control class. This shows that there is an effect of the application of the STAD type cooperative learning model on the mathematical communication skills of Avicenna SMPIT students. The amount of influence based on the calculation of Cohen's effect size is 76% which is included in the medium category.